Fabrication and Structural Integrity Analysis of a Jenang Mixer Machine: A Solution for Modernizing Traditional Indonesian Food Production (Jurnal Teknik Mesin Mechanical Xplore, 2025)
The design and fabrication of the Jenang mixer machine are carried out to enhance the efficiency of household industrial-scale Jenang production. The machine is designed using an engineering approach based on numerical analysis and the Design for Manufacture and Assembly (DFMA) method. The drive power calculation shows a minimum requirement of 2072.7 Watts; therefore, a 3 HP electric motor equipped with a gearbox is used to produce significant torque at low revs. Analysis of the frame strength using static simulations in Fusion 360 software revealed that the machine structure had a safety factor of 15 and a maximum displacement of only 0.006 mm, indicating a robust and stable structure. The fabrication results indicate that the machine comprises 12 principal components and operates reliably in evenly stirring the Jenang dough, making it suitable for small to medium-scale production.